Daisy-head Mayzie - Seuss, Dr. (New York : Harpercollins, 1994)
Young Mayzie McGrew becomes a worldwide sensation when a daisy grows out of the top of her head, and everyone attempts to get rid of it.
Keywords: Humorous stories; Daisies -- Fiction; Stories in rhyme